Test–Retest Reliability of Physiological Variables During Submaximal Seated Upper-Body Poling in Able-Bodied Participants - Ettema, Marlou; Brurok, Berit; Baumgart, Julia Kathrin (Frontiers in Physiology, 2021)
Purpose: To investigate the test-retest reliability of physiological variables across four different test days and four different submaximal exercise intensities during seated upper-body poling (UBP). Methods: Thirteen abled-bodied, upper-body trained men (age 29 ± 3 years; body mass 84 ± 12 kg; height 183 ± 5 cm) performed four submaximal 4-min stages of seated UBP on four separate test days. The four submaximal stages were set at individual power outputs corresponding to a rating of perceived exertion of 9, 11, 13 and 15. The absolute reliability for pairwise test-day comparisons of the physiological variables was investigated with the smallest detectable change percentage (%SDC) and the relative reliability with the interclass correlation coefficient (ICC). Results: Absolute and relative reliability across test day comparisons and submaximal stages were moderate to excellent for all variables investigated (V̇O2 - %SDC range: 5-13%, ICC range: 0.93-0.99; HR - %SDC range: 6-9%, ICC range: 0.91-0.97) other than blood lactate, for which absolute reliability was poor and relative reliability highly variable (%SDC range: 26-69%, ICC range: 0.44-0.92). Furthermore, absolute and relative reliability was consistent across the low to moderate exercise intensity spectrum, and across test days. Conclusion: Absolute and relative test-retest reliability was acceptable for all investigated physiological variables but blood lactate. The consistent test-retest reliability across the exercise intensity spectrum and across test days indicates that a familiarization period to the specific exercise modality may not be necessary. For generalizability, these findings need to be confirmed in athletes with a disability by future large-scale studies.